ANALISA KEPUASAN KERJA, KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN (Studi Kasus Pada Karyawan Bagian Sewing PT Dan Liris) - Resha Dwi Khotimah; Djumali Djumali; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2019)
This study aims to examine the effect of simultaneous and partial of job satisfaction, organizational commitment and work environment as an independent variable on employee turnover intention as the dependent variable. The methodology of this research uses quantitative descriptive. The sampling technique using simple random sampling obtained a sample of 100 employees of PT Dan Liris Sewing section. Data collection using a questionnaire while the data analysis method used is multiple linear regression analysis processed with the help of SPSS version 24. The results showed: (1) F test results showed that job satisfaction, organizational commitment and work environment simultaneously had a positive and significant effect on employee turnover intention at PT Dan Liris. (2) Based on the partial test results the job satisfaction variable has a positive and not significant effect on employees of Sewing section at PT Dan Liris. (3) Based on the partial test results the organizational commitment variable has a positive and not significant effect on employees of Sewing section at PT Dan Liris. (4) Based on the partial test results the work environment variable has a positif and significant effect on employees of Sewing section at PT Dan Liris. Keywords: Job Satisfaction, Organizational Commitment, Work Environment, Turnover Intention